Practice of childhood immunizations among parents and their associated factors in Hulu Langat, Selangor, Malaysia - Che Abdullah, Azreena; Mohd Zulkefli, Nor Afiah; Abd Manaf, Rosliza (Community Health Society Malaysia (CHSM), 2016)
Background: Childhood immunization is one of World Health Organizations (WHO) strategy in reducing children mortality. However there are still existences of unvaccinated children in Malaysia which can be seen by the rising of vaccine preventable diseases. Various factors contributed to parent’s decision on vaccinating their children. The aim of this is to assess parents’ practice on childhood immunizations in Hulu Langat, Selangor. Materials and Methods: A cross sectional study design was conducted from January 2016 till July 2016 where 760 out of 830 respondents participated yielding a response rate of 89.1%. Respondents were selected by cluster random sampling and a pre-tested self-administered questionnaire was used. Result: Majority of the respondents were female (70%), Malay (87%), employed (92%) and graduates of either college or university (99.7%). In this study, 98.2% parents immunized their children. However 14(1.8%) parents in this study did not immunized their children and majority of them gave “vaccinations are dangerous” as their reason of not vaccinating. Conclusion: From this study majority of the parents in Hulu Langat immunized their children and only 14 parents who did not immunize their children. The modifiable factor that influenced their practice is source of information by healthcare provider. This finding can be a baseline data for any health intervention strategies in the future.